Ensino da Física na dança: possibilidades para a educação básica - Silva, Thayane Bezerra da [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
In dance’s world, we always come across fascinating movements, which when well executed take the dancer to high levels of performance. Although Physics is present in all the steps of dance and is responsible for practically all the technique, little is said about this subject, both among dance artists and the public that studies physics. For a better use of this artistic area within basic education and seeking to solve problems such as the lack of motivation to learn physics, we find here a possibility for creative development, with a better use of this artistic area in basic education, particularly dance. Including dance in physics teaching is the focus of our study, analyzing contemporary dance, dance-theater and classical ballet as possibilities, through activities in which the student can have direct perceptions and it is possible to relate the artistic environment with the physics around him.

No mundo da dança nos deparamos com movimentos fascinantes, que quando bem executados levam o bailarino a altos níveis de performance. Embora a física esteja presente em todos os passos e ser a responsável por praticamente toda a técnica, pouco se fala nesse assunto, tanto entre artistas da dança quanto aos estudantes de física. Buscando resolver problemas como a desmotivação para estudar física, discutimos uma possibilidade de desenvolvimento criativo, com um melhor aproveitamento dessa área artística na educação básica, particularmente a dança. A inclusão da dança no ensino da física é o foco desse estudo, analisando como possibilidades a dança contemporânea, a dança-teatro e o ballet clássico, por meio de atividades em que o estudante possa ter percepções diretas e seja possível relacionar o meio artístico com a física a seu redor.
Physics teaching in dance: possibilities for basic education
Keywords: Physics; Dance; Physics teaching; Basic education; Física; Dança; Ensino de física; Educação básica